Husband Support Mediates the Association between Self-Efficacy and Cervical Cancer Screening among Women in the Rural Area of Indonesia - Juwitasari; Ririn Harini; Achmad Ainur Rosyad (Elsevier, 2021)
Objective: Standard cervical cancer screening is seen as the most efficient way of preventing cases of cervical cancer. This study aimed to test indirect husband support pathways and the use of self-efficacy and Visual Inspection with Acetic Acid (VIA) testing among women in Indonesian rural areas. Methods: The research implemented a cross-sectional design carried out in East Java, Indonesia, a remote county. The inclusion criteria were women between the ages of 30 and 50 years, married or women having experienced of having sexual intercourse, have been utilized VIA test at least 3 years ago. The Self-Efficacy Scale and the Husband Help Survey were used to test the interest variable. A structural equation modeling was used to assess the relationship between husband help and VIA test self-efficacy. Results: The study was followed by a total of 219 respondents. Women's mean age was 33.03 years (standard deviation [SD]: 6.44), and the mean age for the husband was 37.51 (SD: 7.45). Just 7.31% had a year ago VIA test, and most (65.75%) had a VIA test within 4 years. A husband's help had the greatest direct impact on the use of Papanicolaou tests, with a 0.312 direction coefficient (P < 0.001). The mediator between the husband's help and the use of VIA tests was self-efficacy (standardized coefficients of the path: 0.123, P < 0.001). Conclusions: Our analysis revealed a route through which husband help influences the use of VIA tests among women in Indonesian rural areas. Providers must consider the effect of husband support on VIA testing in promoting the use of VIA tests among females in Indonesia. One potential communication approach is that providers make improvements to improve the use of VIA tests in supporting self-efficacy.